Discovery of waterbird colonies in North Lampung, Sumatra - Derek A Holmes; Yus Rusila Noor (Indonesian Ornithologists’ Union, 1995)
The Tulang Bawang river with its back swamps, in Lampung province, Sumatra, is identified as a habitat of major importance to waterbirds. There are at least two breeding colonies, one of which may prove to be the largest heronry so far discovered in Indonesia, with between 5,000 and 33,000 pairs of herons and egrets. The most abundant species is Javan Pond-heron Ardeola speciosa, and this is only the second breeding colony of this species to be discovered in Sumatra; it may rank as the largest in Indonesia. It is the third colony to be discovered in Sumatra of Great Egret Casmerodius albus. The first breeding records in Sumatra of Night-heron Nycticorax nycticorax were obtained from one colony, and of Oriental Darter Anhinga melanogaster at the second. The region is also probably the most important in Sumatra, if not in the Sundaic region, for Bronze-winged Jacana Metopidius indicus. Recommendations have been made for Nature Reserve status to be designated at the sites of the two colonies, and for a Game Reserve to cover a much wider area of the feeding grounds and fisheries. It is feared that there has been a major decline in population of both the White-winged Duck Cairina scutulata and the Cotton Pygmy Goose Nettapus coromandelianus, and it is proposed that the latter species should also now be classified as threatened in Indonesia.